2011
DOI: 10.4161/rna.8.5.16022
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Y-box-binding protein 1 (YB-1) and poly(A) binding protein (PABP) in specific regulation ofYB-1mRNA translation

Abstract: YB-1 is a DNA- and RNA-binding protein that regulates expression of many important genes. Its deficiency or excess may pose threats, including malignant cellular transformation and metastasis, which explains the necessity of strict control over its amount at every level. As we showed previously, the 3' untranslated region (UTR) of YB-1 mRNA contains a regulatory element specifically binding to YB-1 and PABP (PABPC1). Also, we showed that YB-1 selectively inhibits YB-1 mRNA translation, while PABP stimulates it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…YB-1-to-RE binding results in inhibition of translation either at the step of mRNA joining to the 43S preinitiation complex or at the previous step of mRNA interaction with translation initiation factors, 23,24 while PABP-to-RE binding causes YB-1 displacement, and hence, activation of translation of YB-1 mRNA. 22,24 It should be noted that the above studies used poly A(-) YB-1 mRNA and revealed only the results of PABP interaction with 3' UTR lacking the poly(A) tail. The current study shows that polyadenylation of YB-1 mRNA stimulates its translation in rabbit reticulocyte lysate (RRL).…”
Section: -25mentioning
confidence: 95%
“…YB-1-to-RE binding results in inhibition of translation either at the step of mRNA joining to the 43S preinitiation complex or at the previous step of mRNA interaction with translation initiation factors, 23,24 while PABP-to-RE binding causes YB-1 displacement, and hence, activation of translation of YB-1 mRNA. 22,24 It should be noted that the above studies used poly A(-) YB-1 mRNA and revealed only the results of PABP interaction with 3' UTR lacking the poly(A) tail. The current study shows that polyadenylation of YB-1 mRNA stimulates its translation in rabbit reticulocyte lysate (RRL).…”
Section: -25mentioning
confidence: 95%
“…YB1 regulates transcription and translation by binding to its recognition motifs in both DNA and RNA to regulate key cell processes such as proliferation, motility, and stemness characteristics (6)(7)(8)(9)(10)(11). Two kinases, RSK and AKT, have been studied as regulators of YB1 function through phosphorylation of YB1 on Serine 102 (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…A Y-box sequence is located directly downstream. The Y-box-binding protein 1 regulates the expression of many important genes (24) and is involved in the development of metastasis in patients with gastric and breast cancer (25). This protein may bind to the hypomethylated region of the GATA4 promoter, and thus regulate its expression, or even act as a partner in metastasis development.…”
Section: Myc Induces Gata4 Promoter Demethylationmentioning
confidence: 99%